2021
DOI: 10.3390/v13040641
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Typing of Human Enteroviruses from Clinical Samples by Entire-Capsid Next Generation Sequencing

Abstract: There are increasing concerns of infections by enteroviruses (EVs) causing severe disease in humans. EV diagnostic laboratory methods show differences in sensitivity and specificity as well as the level of genetic information provided. We examined a detection method for EVs based on next generation sequencing (NGS) analysis of amplicons covering the entire capsid coding region directly synthesized from clinical samples. One hundred and twelve clinical samples from England; previously shown to be positive for E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Phage cocktail persistence in the open field could be improved with specific formulations [ 9 ] and their action can be increased in synergy with the addition with other compounds such as carvacrol [ 20 ] and garlic extract [ 24 ]. Additionally, the phages we isolated can be a useful source of endolysins as an alternative Psa and Pph biocontrol method [ 78 ]; the vast number of functionally uncharacterized ORFs they encode could contribute to further control approaches once their role is elucidated, urging a vast effort to assign function to the unprecedented proteomic diversity harbored by phages [ 67 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phage cocktail persistence in the open field could be improved with specific formulations [ 9 ] and their action can be increased in synergy with the addition with other compounds such as carvacrol [ 20 ] and garlic extract [ 24 ]. Additionally, the phages we isolated can be a useful source of endolysins as an alternative Psa and Pph biocontrol method [ 78 ]; the vast number of functionally uncharacterized ORFs they encode could contribute to further control approaches once their role is elucidated, urging a vast effort to assign function to the unprecedented proteomic diversity harbored by phages [ 67 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, though originally designed to amplify complete capsid protein sequence region of poliovirus (an Enterovirus C. species member), 12 coupled with the findings of this study, we and others have now shown that the PanEV RT-PCR assay can amplify the same region from other enterovirus species (particularly enterovirus species A, B, C, D, and G and rhinovirus species A, B, and C) and canine picornavirus genomes. [13][14][15] We are aware that the diversity of rhinovirus types described here might not be a complete catalog of all the types present in the samples screened or that circulated in the university community during the period sampled. Particularly, the fact that we pooled only 20 μl of each resuspended NP swab sample coupled with the stringent (>2000 nt contig length and >50x coverage; Table 1) cutoff used in our assembly and detection pipeline could have prevented detection of low titer rhinovirus (or other enterovirus) types present in the samples.…”
Section: Discussionmentioning
confidence: 99%
“…species member), 12 coupled with the findings of this study, we and others have now shown that the PanEV RT‐PCR assay can amplify the same region from other enterovirus species (particularly enterovirus species A, B, C, D, and G and rhinovirus species A, B, and C) and canine picornavirus genomes. 13 , 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…We used an echovirus adapted version of the entire capsidcoding region amplification (ECRA) method originally designed for poliovirus by Arita et al [14] and modified for enteroviruses [13,15,16] (Fig. 1A).…”
Section: Entire Capsid-coding Region Amplification By Rt-pcrmentioning
confidence: 99%
“…Routinely generated nucleotide sequencing information about EVs from clinical samples is usually limited to short, partial genomic sequences of VP1 that enable identifying the genotype but have limited use for detailed genetic characterisation. Several approaches to EV NGS have been described previously for sequencing viruses directly from clinical samples and from cell culture isolates with metagenomics or target-specific techniques, still, available E9 virus sequences covering the whole capsid are scarce [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%